Prexasertib, a cell cycle checkpoint kinase 1 and 2 inhibitor, in BRCA wild-type recurrent high-grade serous ovarian cancer: a first-in-class proof-of-concept phase 2 study. Issue 2 (February 2018) - Lee, Jung-Min; Nair, Jayakumar; Zimmer, Alexandra; Lipkowitz, Stanley; Annunziata, Christina M; Merino, Maria J; Swisher, Elizabeth M; Harrell, Maria I; Trepel, Jane B; Lee, Min-Jung; Bagheri, Mohammad H; Botesteanu, Dana-Adriana; et al.
Summary: Background: High-grade serous ovarian carcinoma is characterised by TP53 mutations, DNA repair defects, and genomic instability. We hypothesised that prexasertib (LY2606368), a cell cycle checkpoint kinase 1 and 2 inhibitor, would be active in BRCA wild-type disease. Methods: In an open-label, single-centre, two-stage, proof-of-concept phase 2 study, we enrolled women aged 18 years or older with measurable, recurrent high-grade serous or high-grade endometrioid ovarian carcinoma. All patients had a negative family history of hereditary breast and ovarian cancer or known BRCA wild-type status, measurable disease according to Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1, Eastern Cooperative Oncology Group performance status score 0–2, and adequate haematological, renal, hepatic, and bone-marrow function. Patients received intravenous prexasertib 105 mg/m 2 administered over 1 h every 14 days in 28-day cycles until disease progression, unacceptable toxicity, or withdrawal of consent. The primary endpoint of investigator-assessed tumour response, based on RECIST version 1.1, was assessed per protocol (assessable patients who had undergone CT imaging at baseline and attended at least one protocol-specified follow-up) and by intention to treat. The final analysis of this cohort of patients with BRCA wild-type high-grade serous ovarian carcinoma is reported here. This ongoing trial is registered withClinicalTrials.gov, numberNCT02203513, and continues to enrol patients for the BRCA -mutated ovarian cancer cohort. Findings: Between Jan 20, 2015, and Nov 2, 2016, we enrolled 28 women with a median age of 64 years (IQR 58·0–69·5) who had previously received a median of 5·0 (IQR 2·5–5·0) systemic therapies. Most patients (22 [79%]) had platinum-resistant or platinum-refractory disease. All women received at least one dose of prexasertib, but four (14%) of 28 patients were not assessable for RECIST response. Eight (33%, 95% CI 16–55) of 24 patients assessable per protocol had partial responses. In the intention-to-treat population, eight (29%, 95% CI 13–49) of 28 had a partial responses. The most common (in >10% patients) grade 3 or 4 treatment-emergent adverse events were neutropenia in 26 (93%) of 28 patients, reduced white blood cell count in 23 (82%), thrombocytopenia in seven (25%), and anaemia in three (11%). Grade 4 neutropenia was reported in 22 (79%) patients after the first dose of prexasertib and was transient (median duration 6 days [IQR 4–8]) and recovered without growth-factor support in all cases. The treatment-related serious adverse event of grade 3 febrile neutropenia was reported in two (7%) patients. One patient died during the study due to tumour progression. Interpretation: Prexasertib showed clinical activity and was tolerable in patients with BRCA wild-type high-grade serous ovarian carcinoma. This drug warrants further development in this setting, especially for patients with platinum-resistant or platinum-refractory disease. Funding: Intramural Research Program of the National Institutes of Health and National Cancer Institute.